Arbitrary-directional broadband vibration energy harvesting using magnetically coupled flextensional transducers. (31st July 2018) - Zhao, Lin-Chuan; Zou, Hong-Xiang; Yan, Ge; Zhang, Wen-Ming; Peng, Zhi-Ke; Meng, Guang
Abstract: The frequency and direction of vibration sources in the ambient environment may be variable and uncertain, thus it is significant to enhance the environmental adaptability of the vibration energy harvester. In this paper, a novel design of arbitrary-directional broadband vibration energy harvester (AB-VEH) using magnetically coupled flextensional transducers is proposed. The vibration in arbitrary direction can be converted into magnetic excitation acting on the flextensional transducers to generate electricity. The variation of the nonlinear magnetic force with the spatial position of the magnet oscillator is provided and the electromechanical coupling dynamical model of AB-VEH is developed. The experiments are carried out to evaluate the performance of the harvester from several representative excitation directions in three-dimensional space. The output maximum average power is from 10 to 174 μ W with the variation of excitation directions (acceleration amplitude is 0.8 g, frequency range of 5 –30 Hz). The results indicate that the AB-VEH is capable of harvesting energy from vibration sources in broad bandwidth and arbitrary direction. Moreover, the flextensional transducers of AB-VEH have high robustness, and the AB-VEH has a better environmental adaptability.